2020
DOI: 10.2196/17331
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virtual Reality in Improving Health Outcomes for Community-Dwelling Older Adults: Systematic Review

Abstract: Background Virtual reality (VR) delivered through immersive headsets creates an opportunity to deliver interventions to improve physical, mental, and psychosocial health outcomes. VR app studies with older adults have primarily focused on rehabilitation and physical function including gait, balance, fall prevention, pain management, and cognition. Several systematic reviews have previously been conducted, but much of the extant literature is focused on rehabilitation or other institutional settings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 70 publications
3
91
0
2
Order By: Relevance
“…Second, the external variables we chose for this study (fall-related self-efficacy and self-avoidance goals) were psychological rather than contextual variables. History of falls (ie, any fall event experienced by older adults during a specified period of time) may be a relevant variable to include in future studies because history of falls was shown to influence older adults’ behaviors in VR training [ 61 ]. Investigating other variables from the unified theory of acceptance and use of technology [ 26 , 36 ] might also be relevant to a better understanding of acceptance of the VRH used to prevent falls.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the external variables we chose for this study (fall-related self-efficacy and self-avoidance goals) were psychological rather than contextual variables. History of falls (ie, any fall event experienced by older adults during a specified period of time) may be a relevant variable to include in future studies because history of falls was shown to influence older adults’ behaviors in VR training [ 61 ]. Investigating other variables from the unified theory of acceptance and use of technology [ 26 , 36 ] might also be relevant to a better understanding of acceptance of the VRH used to prevent falls.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the external variables we chose for this study (fall-related self-efficacy and self-avoidance goals) were psychological rather than contextual variables. History of falls (ie, any fall event experienced by older adults during a specified period of time) may be a relevant variable to include in future studies because history of falls was shown to influence older adults' behaviors in VR training [61]. Investigating other variables from the unified theory of acceptance and use of technology [26,36] might also be relevant to a better understanding of acceptance of the VRH used to prevent falls.…”
Section: Current Limitations and Directions For Future Studiesmentioning
confidence: 99%
“… 33 Additionally, research with older adults does not always assess side effects from using VR. 34 There is a need to increase our understanding of side effects from using VR in older adults, particularly with the increased use of HMDs for therapy in older clinical populations.…”
Section: Introductionmentioning
confidence: 99%